2020
DOI: 10.1182/blood-2020-133933
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Induced Memory-like NK Cells Exhibit Massive Expansion and Long-Term Persistence after Infusion Post-Haploidentical Stem Cell Transplantation: A Report of the First Three Cases in a Phase I Trial

Abstract: Background Relapse of acute myeloid leukemia (AML) after allogeneic stem cell transplant has a poor prognosis with limited treatment options. Cytokine-induced memory like natural killer (CIML NK) cells are a novel therapy with enhanced cytotoxicity independent of KIR ligand interactions able to induce remission of relapsed/refractory AML (Romee et al, Science TM 2016). We are evaluating the safety and potential efficacy of donor-derived CIML NK cells in patients with relapsed myeloid malignancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The overall response rate (ORR) was 55% (5/9), with 45% of CR/CRi (4/9). Preliminary data from an ongoing clinical trial with CIML NK cells in patients with relapsed AML after HSCT showed a massive expansion rate with persistence of up to 6 months 92 …”
Section: Results Of Clinical Trials In Hematological Malignanciesmentioning
confidence: 99%
“…The overall response rate (ORR) was 55% (5/9), with 45% of CR/CRi (4/9). Preliminary data from an ongoing clinical trial with CIML NK cells in patients with relapsed AML after HSCT showed a massive expansion rate with persistence of up to 6 months 92 …”
Section: Results Of Clinical Trials In Hematological Malignanciesmentioning
confidence: 99%
“…Therapeutic NK cell products can be derived from placental/umbilical cord blood, peripheral blood, induction of stem cells, or immortalized cell lines, which then can be expanded using a variety of methods. For example, NK cells can be expanded in vivo and stimulated with IL-2, generating cytokine-induced memory-like NK cells that have been shown to persist in patients for over six months ( 172 , 173 ). Alternatively, NK cells can be expanded using feeder cells, like K562 expressing membrane-bound IL-21 and 4-1BB ligand, which interact with NK cell-surface receptors to induce proliferation and activation ( 174 , 175 ).…”
Section: Synergistic Combinations With Nk Cell Productsmentioning
confidence: 99%
“…Ongoing clinical studies have shown that the prolonged persistence of the adoptively transferred CIML NK cells is associated with the attainment of clinical responses (6,21,(61)(62)(63). Upon their adoptive transfer into an immune compatible environment in the context of an allogeneic HCT in a phase 1 clinical trial, the infusion of CIML NK cells resulted in a massive expansion of the NK cell compartment that persisted for up to 6 months (26). The use of the CIML NK platform for the prevention of post-allogeneic HCT relapse of myeloid disease is concurrently being explored (65).…”
Section: In Vivo Persistence Of Nk Cells After Infusionmentioning
confidence: 99%